Survey of the invasive alien pink salmon (Oncorhynchus gorbuscha) for infective agents in the Fennoscandian Rivers Tana and Neiden - Holopainen, Riikka; Kantala, Tuija; Korkea-aho, Tiina; Heikkinen, Petra; Oksanen, Antti; Orell, Panu; Viljamaa-Dirks, Satu (Elsevier BV, 2025)
Pink salmon (Oncorhynchus gorbuscha, Walbaum 1792) is an invasive alien species in the Fennoscandian rivers, and its growing populations cause concern for their impact on the native salmonids and river ecosystems. One of the major concerns is fish diseases and the potential ability of pink salmon to transmit pathogens to the native salmonid species. In this study, pink salmon were sampled during their spawning migration in the Rivers Tana and Neiden in northern Norway and Finland in 2021. The fish were surveyed for viral hemorrhagic septicemia virus (VHSV), infectious pancreatic necrosis virus (IPNV), infectious salmon anemia virus (ISAV), salmonid alphavirus (SAV), piscine orthoreovirus (PRV), Renibacterium salmoninarum, and Gyrodactylus salaris. No viral diseases or infections with R. salmoninarum or G. salaris were detected. However, 23 % of the fish were found infected with a parasitic roundworm, Hysterothylacium aduncum. Additionally, external anomalies, such as hemorrhages or lesions in the skin, were observed in 35 % of the fish studied, and some of the fish exhibited degenerative myopathy. Based on this study, pink salmon appears not to pose a high infection risk to the native salmonid fish populations in the Rivers Tana and Neiden. Nevertheless, the results demonstrate that pink salmon have the potential to carry salmonid pathogens. More information on the susceptibility of pink salmon to different pathogens and on the overall effect this invasive species has on native fish species is needed. As the number of migrating pink salmon in the Fennoscandian rivers appears to increase, the potential risk of parasites and other pathogens spreading between fish species will also rise.
Keywords: pink salmon; Oncorhynchus gorbuscha; disease survey; Hysterothylacium aduncum; River Tana; River Neiden